(untitled) (Journal of Civil Engineering Researchers, 2021)
A chain reaction or collapse-spreading in which, under certain causes, local damage occurs in a relatively small area of the structure and under certain conditions this local damage spreads to other parts of the structure and ultimately leads to overall collapse of the structure is called progressive collapse. The main feature of this phenomenon is that the final collapse is not commensurate with the initial collapse; severe incidents such as terrorist attacks, vehicle collisions and explosions, etc. often damage the building and collapse in one or more vertical bearing parts leads to a serious threat. The following article provides an overview of the main research and developments in 2019 and 2020 regarding progressive collapse such as progressive collapse assessment, experimental testing, and numerical modeling.